The association between serum heat shock protein 72 and intestinal permeability with intestinal microbiota and clinical severity in patients with cerebral infarction - Zhu, Jiahui; Dai, Yijie; Tang, Bo; Zhang, Hao (Frontiers in Medicine, 2024)
Objectives We aimed to compare serum heat shock protein 72 (HSP72) and intestinal permeability in patients with cerebral infarction (CI) and healthy individuals to reveal their correlations and link to gut microbiota alterations and clinical severity of CI. Methods and results Stool samples of 50 patients with CI and 46 healthy volunteers were analyzed through 16S rRNA gene sequencing to characterize intestinal flora profiles. Serum HSP72 and zonulin were assayed using enzyme-linked immunoassay (ELISA). The obtained data were then subjected to comparative and correlative analysis. We found that the levels of zonulin and serum HSP72 were significantly higher in the CI group compared to the healthy group. Serum HSP72 and zonulin levels were positively correlated in the CI group and correlated positively with the clinical severity of CI. β diversity showed significant differences in intestinal microbiota composition between the two groups. In the CI patient group, the abundance of bacteria Eubacterium_fissicatena_group, Eubacterium_eligens_group, and Romboutsia manifested a remarkably positive correlation with serum HSP72. The abundance of bacteria Eubacterium_fissicatena_group and Acetivibrio had a significantly positive correlation with zonulin levels. Conclusion Our findings indicated that an increase in serum HSP72 and zonulin levels was manifested in patients with CI and was related to specific gut microbiota alterations and the clinical severity of CI.